Continuous-feed nanocasting process for the synthesis of bismuth nanowire composites. Issue 91 (2nd November 2017) - Vandaele, K.; Heremans, J. P.; Van Driessche, I.; Van Der Voort, P.; De Buysser, K.
Abstract : We present a novel, continuous-feed nanocasting procedure for the synthesis of bismuth nanowire structures embedded in the pores of a mesoporous silica template. Abstract : We present a novel, continuous-feed nanocasting procedure for the synthesis of bismuth nanowire structures embedded in the pores of a mesoporous silica template. The immobilization of a bismuth salt inside the silica template from a diluted metal salt solution yields a sufficiently high loading to obtain electrically conducting bulk nanowire composite samples after reduction and sintering the nanocomposite powders. Electrical resistivity measurements of sintered bismuth nanowires embedded in the silica template reveal size-quantization effects.